" Evaluation of monitoring and evaluation department of the universal basic education board of Oyo state " (2010)
" It is a known fact that basic education level of any country goes a long way in influencing the country's development. It is on this premise, that this study critically evaluated the monitoring and evaluation department of the Universal Basic Education Board of Oyo State. The purpose of the study was to determine the extent to which some of the objectives of the Monitoring and Evaluation (M&E) department have been achieved. The sample consisted of 12 (public and private) pre-primary, primary and Junior Secondary (JSS) Schools in each of the ten purposively selected Local Government Areas (L. G.A) of Ibadan and Ibarapa central in Oyo State. One hundred and 20 teachers and twenty teacher supervisors making a total of 140 respondents participated. A descriptive survey design was used in the study. Two instruments tagged 'Teacher/Headteacher/Principal Questionnaire (THPQ) and 'Supervisor' Questionnaire (SQ) were used to generate the data. The data generated were analysed using frequency counts and percentages. The findings revealed that finance was the major hindrance to effective monitoring of schools and that UBE programme contended with a lot of problems such as inadequate infrastructure, poor remuneration and poor supervision and monitoring. Further, findings also showed that attendance of teachers at seminars and workshops was about twice in a term, not encouraging if the teachers were to cope with the new innovations that abound within the education sector. It was, therefore, recommended that government should improve the effectiveness of the M& E departments for effective and strategic planning, by providing adequate funds, infrastructure and instructional facilities. Also, the training of staff for effective M&E processes should be incorporated into the educational system. "